2009
DOI: 10.1111/j.1939-165x.2009.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aspiration and nonaspiration techniques for obtaining cytologic samples from the canine and feline spleen

Abstract: These results suggest the nonaspiration technique is a superior method for obtaining a high-quality cytologic specimen from the canine and feline spleen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
0
26
1
Order By: Relevance
“…All ultrasonographic examinations and ultrasound‐guided sample collection was performed using an 8 MHz curvilinear transducer. Fine‐needle sample collection was performed using 22‐gauge, 1.5‐inch‐long needles using a nonaspiration technique . A needle was guided into the spleen and then gently moved up and down along the needle tract in an attempt to harvest cells; no negative pressure was applied to the syringe .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All ultrasonographic examinations and ultrasound‐guided sample collection was performed using an 8 MHz curvilinear transducer. Fine‐needle sample collection was performed using 22‐gauge, 1.5‐inch‐long needles using a nonaspiration technique . A needle was guided into the spleen and then gently moved up and down along the needle tract in an attempt to harvest cells; no negative pressure was applied to the syringe .…”
Section: Methodsmentioning
confidence: 99%
“…Fine‐needle sample collection was performed using 22‐gauge, 1.5‐inch‐long needles using a nonaspiration technique . A needle was guided into the spleen and then gently moved up and down along the needle tract in an attempt to harvest cells; no negative pressure was applied to the syringe . Splenic nodules that had characteristic ultrasonographic appearance of myelolipomas were not routinely sampled .…”
Section: Methodsmentioning
confidence: 99%
“…In another study of diagnostic samples from 35 dogs, cytopathological and histopathological diagnoses agreed completely in 18 of 35 dogs (51%), partially in 3 of 35 dogs (9%) and were in disagreement in 14 of 35 dogs (40%) (Watson et al 2011 ). Non-aspiration techniques appear to be superior during FNA of the spleen in both cats and dogs because they produce samples of greater cellularity and less blood contamination (Leblanc et al 2009 ).…”
Section: A Closer Look At Sampling Specific Organs Livermentioning
confidence: 97%
“…A major advantage of the non-aspiration technique is reduced blood contamination when sampling highly vascular tissues, such as the spleen (Leblanc et al 2009 ), kidney and liver (Savage et al 1995, Raskin & Meyer 2015. Non-aspiration has been found to have similar or greater sensitivity to that of aspiration for a variety of tissues, including the spleen and abdominal lymph nodes (Menard & Papageorges 1995, Savage et al 1995, Wallace et al 2001, Sigstad et al 2004, Leblanc et al 2009, Sajeev & Siddaraju 2009, Jahromi et al 2015. In contrast, other studies have shown an increased diagnostic yield in the liver (Haseler et al 2011 ) and pancreas (Kinney et al 1993 ) when using aspiration as opposed to nonaspiration techniques.…”
Section: Aspiration Techniquementioning
confidence: 99%
“…62 It should be noted that these statements are derived from a study involving 24 dogs and only seven cats, although it was felt by the authors that the results from the feline splenic samples mirrored those of their canine counterparts. 62 Several aspirates should be collected and, if ultrasound indicates the presence of central necrosis, samples should also be obtained at the margin of the lesion. 63 Where possible, it is helpful to stain and examine one or two slides prior to submission to a commercial laboratory to ensure samples have sufficient cellularity.…”
Section: Miscellaneous Conditions Infarctionmentioning
confidence: 99%